Skin microbiome profile in people living with HIV/AIDS in Cameroon - Ogai, Kazuhiro; Nana, Benderli Christine; Lloyd, Yukie Michelle; Arios, John Paul; Jiyarom, Boonyanudh; Awanakam, Honore; Esemu, Livo Forgu; Hori, Aki; Matsuoka, Ayaka; Nainu, Firzan; Megnekou, Rosette; Leke, Rose Gana Fomban; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
The presence of pathogens and the state of diseases, particularly skin diseases, may alter the composition of human skin microbiome. HIV infection has been reported to impair gut microbiome that leads to severe consequences. However, with cutaneous manifestations, that can be life-threatening, due to the opportunistic pathogens, little is known whether HIV infection might influence the skin microbiome and affect the skin homeostasis. This study catalogued the profile of skin microbiome of healthy Cameroonians, at three different skin sites, and compared them to the HIV-infected individuals. Taking advantage on the use of molecular assay coupled with next-generation sequencing, this study revealed that alpha-diversity of the skin microbiome was higher and beta-diversity was altered significantly in the HIV-infected Cameroonians than in the healthy ones. The relative abundance of skin microbes such as Micrococcus and Kocuria species was higher and Cutibacterium species was significantly lower in HIV-infected people, indicating an early change in the human skin microbiome in response to the HIV infection. This phenotypical shift was not related to the number of CD4 T cell count thus the cause remains to be identified. Overall, these data may offer an important lead on the role of skin microbiome in the determination of cutaneous disease state and the discovery of safe pharmacological preparations to treat microbial-related skin disorders.